Конек-горбунок: [сказка] / П. П. Ершов - Ершов Петр Павлович (Книги - мои друзья, 2016)
Экземпляры: ДО (20200527) / Инвентарный номер: 64634 / Цена: 110.00 / Сис.шифр: 84(2Рос=Рус) / Авт.знак: Е 80 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)